2022
DOI: 10.3390/d14070555
|View full text |Cite
|
Sign up to set email alerts
|

Bird Communities Vary under Different Urbanization Types—A Case Study in Mountain Parks of Fuzhou, China

Abstract: Bird habitats are becoming increasingly fragmented as a result of rapid urbanization. As one of the essential refuges for urban bird communities, mountain parks are of practical significance for studying the spatial changes of birds, which can inform the future planning of mountain park planning. In this study, we assessed the α, β, and functional diversity of bird communities in mountain parks in Fuzhou, China, at three levels of urbanization (urban, peri-urban, suburban) and explored how diversity (abundance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 60 publications
1
5
0
Order By: Relevance
“…Contrary to our initial expectations based on published evidence on the composition of tropical avian assemblages along urbanization gradients (Sanz and ), species richness and diversity did not differ between the urban and the suburban protected site. Overall bird abundance tended to be higher at the urban protected site compared to the suburban one, in accordance with most previous studies (Batáry et al 2018;Xu et al 2022). However, the difference in abundance was to some extent due the fact that the Palmchat, a common Haitian avian species, was rare at WFER, whereas it was largely predominant at UNPM.…”
Section: Species Richness Diversity and Abundancesupporting
confidence: 92%
“…Contrary to our initial expectations based on published evidence on the composition of tropical avian assemblages along urbanization gradients (Sanz and ), species richness and diversity did not differ between the urban and the suburban protected site. Overall bird abundance tended to be higher at the urban protected site compared to the suburban one, in accordance with most previous studies (Batáry et al 2018;Xu et al 2022). However, the difference in abundance was to some extent due the fact that the Palmchat, a common Haitian avian species, was rare at WFER, whereas it was largely predominant at UNPM.…”
Section: Species Richness Diversity and Abundancesupporting
confidence: 92%
“…Erdelen (1984) [ 58 ] found that bird species richness and diversity were often related to vegetation structure rather than just woody species richness. The planning and design of urban mountain parks needs to provide for not only the recreational needs of tourists but also issues such as providing habitats for wildlife [ 22 ]. Therefore, various types of vegetation structures have emerged in urban mountain parks, such as dense forests, sparse forests, shrubs, grasslands, and waterfronts as five typical vegetation habitat types, which represent an increase in structural complexity.…”
Section: Discussionmentioning
confidence: 99%
“…Fuzhou has a richness of bird resources, with 455 species recorded in the China Birding Record Center ( , accessed on 13 August 2022) as of August 2022. Therefore, the conservation of wild bird resources in Fuzhou is significant not only for the improvement of local biodiversity but also for the protection of all wild bird species along their migratory routes through Fuzhou [ 22 ]. Unlike ordinary urban parks, urban mountain parks are usually built on the unique environment of special topography and natural ecology and are a major part of the urban green space system [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the sample size of the selected urban parks (n = 9) was quite small, the study was conducted only during a single winter and only in one city. Additionally, some other factors, such as noise level [ 77 ], artificial light [ 78 ], recreational activities [ 63 ], other guilds of birds [ 79 ], and vegetation habitats [ 80 ], may influence winter bird assemblage structure in urban parks.…”
Section: Discussionmentioning
confidence: 99%